2023
DOI: 10.1093/jleuko/qiad058
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain polyphosphates inhibit type I interferon signaling and augment LPS-induced cytokine secretion in human leukocytes

Anniina Pirttiniemi,
Krishna Adeshara,
Natalie Happonen
et al.

Abstract: Inorganic polyphosphates are evolutionarily conserved bioactive phosphate polymers found as various chain lengths in all living organisms. In mammals, polyphosphates play a vital role in the regulation of cellular metabolism, coagulation, and inflammation. Long-chain polyphosphates are found along with endotoxins in pathogenic gram-negative bacteria and can participate in bacterial virulence. We aimed to investigate, whether exogenously administered polyphosphates modulate human leukocyte function in vitro by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Pirttiniemi et al . [ 46 ] found that cells treated with long‐chain polyP (P700) treatment is associated with the activation of mTOR activation in human leukocytes and Wang et al . [ 26 ] reported that polyP stimulates mTOR in mammary cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Pirttiniemi et al . [ 46 ] found that cells treated with long‐chain polyP (P700) treatment is associated with the activation of mTOR activation in human leukocytes and Wang et al . [ 26 ] reported that polyP stimulates mTOR in mammary cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…While the literature is scarce, the toxicity of long chain polyP in mammalian cells has already been suggested by some authors. For example, as previously mentioned, long chains of the polymer induce major effects in the transcriptome, proteome, and phosphatome of mammalian cells (Bondy-Chorney et al, 2020;Pirttiniemi et al, 2023), which could be associated with substantial changes in cell physiology, including viability. Furthermore, it has recently been published that increased release of polyP by astrocytes causes toxicity to motoneurons (Arredondo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While the length of mammalian polyP still remains controversial; it has been proposed that this polymer is usually found in two pools in cell lines: very long chains, and short lengths (Kumble and Kornberg, 1995). We decided to use short chains of polyP to conduct all our studies because, based on the bibliography, long chains of the polymer induce major effects in the transcriptome, proteome, and phosphatome of mammalian cells (Bondy-Chorney et al, 2020;Pirttiniemi et al, 2023). Moreover, the data included in this manuscript show that the expression of MitoPPK is lethal for SH-SY5Y cells.…”
Section: Ppx and Ppn Enzymatic Activitymentioning
confidence: 99%